Skuteczność zarządzania wiedzą w przedsiębiorstwach wiedzy - Nogalski, Bogdan; Kowalczyk, Adam (Effectiveness of Knowledge Management in Knowledge Companies, 2006)
"The article - on the basis of empirical research - concentrates on proving the thesis: ""Polish consulting companies ('knowledge companies') cannot efficiently manage the knowledge which is their core resource and most important product"". In order to prove the thesis, the authors use their own tools, i.e. Knowledge Management Conception and Knowledge Management Audit. As a result of the research, knowledge management in consulting companies seems to be a set of accidental, unaware and aimless activities. The activities are not comprehensive as well as do not meet the economical virtue. "
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 174-183